Polyphenols: Distribution, Extraction, Bioactivity, Biotransformation, and Application - Wei, Rong-Rui; Ma, Qin-Ge; Liu, Wen-Min; Zhang, Zhi-Hui (Combinatorial Chemistry & High Throughput Screening, 2026)
<span class=
Keywords: Polyphenols